Analysis of the Influence of Financial Distress, Capital Structure, Complexity of Company Operations, Auditor Opinion and KAP's Reputation on Audit Delay - Clara Liany Tampubolon; Afrizal, Afrizal; Yuliusman, Yuliusman (PT FORMOSA CENDEKIA GLOBAL, 2024)
The aim of this research is to analyze the influence of financial distress, capital structure, company operational difficulties, auditor opinion, and KAP reputation on audit delay simultaneously and partially. Sampling used purposive sampling by considering a population of 84 property & real estate sector companies listed on the Indonesia Stock Exchange in 2020-2022. 71 companies were selected for three years or 213 eligible data. This quantitative research uses multiple linear regression analysis techniques using IBM SPSS version 26 software. The findings of this research reveal that financial distress, capital structure and company operational complexity have a significant effect on audit delay. On the other hand, the auditor's opinion and KAP reputation do not show any influence on audit delay.